2016
DOI: 10.4269/ajtmh.15-0908
|View full text |Cite
|
Sign up to set email alerts
|

National Malaria Prevalence in Cambodia: Microscopy Versus Polymerase Chain Reaction Estimates

Abstract: Abstract. Accurate information regarding malaria prevalence at national level is required to design and assess malaria control/elimination efforts. Although many comparisons of microscopy and polymerase chain reaction (PCR)-based methods have been conducted, there is little published literature covering such comparisons in southeast Asia especially at the national level. Both microscopic examination and PCR detection were performed on blood films and dried blood spots samples collected from 8,067 individuals e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(30 reference statements)
0
5
0
4
Order By: Relevance
“…A series of large-scale malaria surveys (Cambodia Malaria Surveys [CMS]) conducted in 2004 (CMS2004, 3,363 households), 2007 (CMS2007, 2,923 households), 2010 (CMS2010, 3,802 households), and 2013 (CMS2013, 3,286 households) conducted by the CNM and Malaria Consortium, further supports the declines in malaria prevalence (all species) detected by both microscopic examination and PCR 17. These surveys, focused on populations at the highest risk determined by stratifying, first, by the level of risk of the provinces, and then by distance from the forests demonstrated that the prevalence of all Plasmodium infections detected by microscopy declined in each successive national survey since 2004.…”
Section: Epidemiological Data On Vivax Malaria In Cambodiamentioning
confidence: 75%
“…A series of large-scale malaria surveys (Cambodia Malaria Surveys [CMS]) conducted in 2004 (CMS2004, 3,363 households), 2007 (CMS2007, 2,923 households), 2010 (CMS2010, 3,802 households), and 2013 (CMS2013, 3,286 households) conducted by the CNM and Malaria Consortium, further supports the declines in malaria prevalence (all species) detected by both microscopic examination and PCR 17. These surveys, focused on populations at the highest risk determined by stratifying, first, by the level of risk of the provinces, and then by distance from the forests demonstrated that the prevalence of all Plasmodium infections detected by microscopy declined in each successive national survey since 2004.…”
Section: Epidemiological Data On Vivax Malaria In Cambodiamentioning
confidence: 75%
“…A RCD pode demandar um esforço logístico grande dos órgãos de vigilância, além de seu alto custo; em adição, os métodos convencionais de diagnóstico (microscopia e o RDT), podem não detectar infecções com baixas cargas parasitárias que são potencialmente viáveis para manter a transmissão do parasito (Okell et al, 2012;Lek et al, 2016). Em uma recente publicação acerca revisão de dados da prevalência de malária no Camboja, a fim de comparar os resultados de microscopia em relação ao PCR; de forma similar aos nossos achados, verificou-se que o método molecular detecta aproximadamente o dobro de infecções por P. vivax em comparação à microscopia convencional.…”
Section: Marcadores Polimórficosunclassified
“…Em uma recente publicação acerca revisão de dados da prevalência de malária no Camboja, a fim de comparar os resultados de microscopia em relação ao PCR; de forma similar aos nossos achados, verificou-se que o método molecular detecta aproximadamente o dobro de infecções por P. vivax em comparação à microscopia convencional. Os autores ainda sugerem que a estratégia de RCD baseada somente na microscopia pode deixar de identificar uma grande proporção de reservatórios da infecção, especialmente em áreas de baixa transmissão (Lek et al, 2016). Em uma recente publicação referente a três análises transversais para se identificar malária na Tailândia, Baum e colaboradores 2016relataram que o qPCR identificou 14 vezes mais infecções pelo plasmódio quando comparado à microscopia convencional e que, cerca de 90% das infecções diagnosticas pelo método molecular foram subpatentes e provenientes de indivíduos assintomáticos.…”
Section: Marcadores Polimórficosunclassified
See 2 more Smart Citations